Case report and literature review: primary hepatic leiomyosarcoma with misdiagnosis and SDHB positive expression - Lu, Chengbin; Ding, Wenchao; Ma, Xiaoli; Xu, Benmo; Luo, Zongyan; Li, Can; Yang, Sinan; Yang, Jinye; Shi, Yuanlong; Bai, Yufan (Frontiers in Oncology, 2025)
BackgroundPrimary hepatic leiomyosarcoma (PHL) is an extremely rare malignancy often misdiagnosed due to nonspecific imaging features overlapping with cholangiocarcinoma. This case highlights diagnostic challenges and the potential association of SDHB positivity with PHL prognosis.Case PresentationA middle-aged male presented with an asymptomatic liver mass. Preoperative CT/MRI revealed a 10-cm lesion with progressive heterogeneous enhancement and delayed capsular enhancement, initially diagnosed as cholangiocarcinoma. Left hepatic lobectomy confirmed PHL. Immunohistochemistry showed SDHB positivity and low Ki67 (15%). The patient recovered well with no recurrence at 6-month follow-up.ConclusionsPHL can radiologically mimic cholangiocarcinoma, necessitating inclusion in differential diagnoses for “cholangiocarcinoma-like” liver masses. SDHB positivity may indicate favorable tumor biology, but further studies are needed to validate its prognostic value. Surgical resection remains curative for localized PHL.